Emerging antigenic variants at the antigenic site Sb in pandemic A(H1N1)2009 influenza virus in Japan detected by a human monoclonal antibody. - Mayo Yasugi; Ritsuko Kubota-Koketsu; Akifumi Yamashita; Norihito Kawashita; Anariwa Du; Ryo Misaki; Motoki Kuhara; Naphatsawan Boonsathorn; Kazuhito Fujiyama; Yoshinobu Okuno; Takaaki Nakaya; Kazuyoshi Ikuta (PLoS ONE, 2013)
The swine-origin pandemic A(H1N1)2009 virus, A(H1N1)pdm09, is still circulating in parts of the human population. To monitor variants that may escape from vaccination specificity, antigenic characterization of circulating viruses is important. In this study, a hybridoma clone producing human monoclonal antibody against A(H1N1)pdm09, designated 5E4, was prepared using peripheral lymphocytes from a vaccinated volunteer. The 5E4 showed viral neutralization activity and inhibited hemagglutination. 5E4 escape mutants harbored amino acid substitutions (A189T and D190E) in the hemagglutinin (HA) protein, suggesting that 5E4 recognized the antigenic site Sb in the HA protein. To study the diversity of Sb in A(H1N1)pdm09, 58 viral isolates were obtained during the 2009/10 and 2010/11 winter seasons in Osaka, Japan. Hemagglutination-inhibition titers were significantly reduced against 5E4 in the 2010/11 compared with the 2009/10 samples. Viral neutralizing titers were also significantly decreased in the 2010/11 samples. By contrast, isolated samples reacted well to ferret anti-A(H1N1)pdm09 serum from both seasons. Nonsynonymous substitution rates revealed that the variant Sb and Ca2 sequences were being positively selected between 2009/10 and 2010/11. In 7,415 HA protein sequences derived from GenBank, variants in the antigenic sites Sa and Sb increased significantly worldwide from 2009 to 2013. These results indicate that the antigenic variants in Sb are likely to be in global circulation currently.